Diffraction grating integrated on micromachined stepper motor for diversity implementation in imaging spectroscopy - Muttikulangara, Sanathanan Swaminathan (2020)
This paper reports a monolithic fabrication of a MEMS rotary stepper motor integrated with a highly efficient diffraction grating to obtain optical transfer function diversity. The rotational motion is achieved by three phase electrostatic actuation mechanism that allows precise stepping motion which is difficult to attain with classical actuation like comb-drive design that depends on the structural resonant frequency. The micro-motor design is based on flexure mechanism to avoid frictional effects and getting the maximum angular stroke. The diffraction grating is fabricated separately by replication technique on a photosensitive material, SU-8 which becomes hard when it is cured. Finally, the replicated diffraction grating is bonded to the micro-actuator using UV-curable glue.